Examining the jurisprudential and legal foundations of the unified opinions No. 733 and 810 of the Supreme Court, with an emphasis on the theory of "expectation damages" in Common Law, and its comparison with Iranian law and Imami jurisprudence. - ali yarinejad (پژوهش‌های فقهی مسائل مستحدثه)
The Unified Precedent Ruling No. 811 of the Supreme Court, which to some extent elucidates certain aspects of Unified Precedent Ruling No. 733, has been critically examined from various perspectives, particularly regarding its legal foundations. In this ruling, the Supreme Court adopted the criterion of objective inflation as a measure to compensate the price paid by the buyer, aiming to place the buyer in a position as if the contract had not been nullified, thereby maintaining the post-contractual status quo. This approach is akin to the doctrine of expectation damages and the concept of anticipated benefit in common law and certain European contract law principles. In this research, using an analytical-descriptive method and relying on library resources and judicial rulings, the aforementioned rulings have been examined and analyzed. The findings of the study indicate that the Supreme Court's approach in Ruling No. 811 is defensible both from the perspective of Iranian law and Imami jurisprudence. This approach can serve as a basis for establishing a unified rule in similar cases and can be utilized as a consistent criterion in analogous legal proceedings.